2002
DOI: 10.1097/00002060-200208000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of a Patient with Heat Stroke

Abstract: The recent death of a famous football player raised public awareness of the fatal nature of heat stroke, which is actually the third leading cause of death among American athletes. We present a typical case of heat stroke to illustrate its clinical manifestation and recovery process; risk factors, treatment options, and the importance of prevention are also discussed. Although heat stroke is not a common admission diagnosis for inpatient rehabilitation, physiatrists need to be aware of its pathophysiology, reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…One case report showed a patient displayed child-like behaviors with limited memory four months post-injury. 13 Even four years after incident, this patient was confined to a wheelchair with only partial mental abilities. This case suggests the possibility of a poor neurological prognosis following EHS due to damage incurred at the time of injury.…”
Section: Neurological Systemmentioning
confidence: 95%
See 1 more Smart Citation
“…One case report showed a patient displayed child-like behaviors with limited memory four months post-injury. 13 Even four years after incident, this patient was confined to a wheelchair with only partial mental abilities. This case suggests the possibility of a poor neurological prognosis following EHS due to damage incurred at the time of injury.…”
Section: Neurological Systemmentioning
confidence: 95%
“…It has been reported that some patients demonstrate or claim that they have had several minutes of lucid behavior just prior to or after collapse; 5 however, CNS abnormality is often the primary marker, or the first visible sign, of EHS. [2][3][4][6][7][8][9][10][11][12][13][14][15][16] There are no premonitory signs or symptoms that consistently forewarn EHS, although some report that patients experience prodromal symptoms. 4 Figure 1 -Organs of the body possibly affected by the hyperthermia of EHS.…”
Section: Signs and Symptoms Of Exertional Heat Strokementioning
confidence: 99%
“…Previous clinical descriptions of EHS presentation and recovery have limited generalizability, due to small patient populations [12,30,31], and often focus on the most severe or fatal forms of injury [11,32]. This study includes a much larger cohort, and includes all available cases without regard for an arbitrary severity designation.…”
Section: Similar Studies and Analysis Of Ehs Presentation And Recoverymentioning
confidence: 99%
“…Classical heat stroke is usually caused by exposure to sustained high temperatures, especially when the humidity is high; the most susceptible victims are elderly patients suffering with comorbid conditions such as diabetes, congestive heart failure, malnutrition or dehydration2). When the ambient temperature is higher than the core body temperature, sweating with vaporization accounts for almost all of heat loss, but when the humidity exceeds 75%, sweating becomes inefficient3).…”
Section: Discussionmentioning
confidence: 99%
“…Brain dysfunction is invariably present and other complications that fall within the category of multiorgan dysfunction syndrome such as rhabdomyolysis, acute renal failure, hepatic failure, myocardial injury and DIC can be life threatening2). Although mild hepatic injury that is represented by elevated transaminase levels is known to be common, fulminant liver failure leading to a death has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%